Fatwa Sesat Syiah dan Legitimasi Kekerasan - Wildan Imaduddin Muhammad (Ri'ayah: Jurnal Sosial dan Keagamaan, 2017)
Abstract Recently, Shi’a-Sunni’s controversy in Indonesia increase dramatically as occurring as geo-political clash in the Middle East, particularly between Saudi Arabia and Iran. The culmination of Indonesian Shi’a’s conflict is assigned by expulsion several communities from their home and village. Afterward, that’s discrimination is legitimated by the book of MUI entitled Mengenal dan Mewaspadai Penyimpangan Syi’ah di Indonesia. This article aims to review the book’s contents by using linguistic philosophy in form of Stephen Toulmin’s theory of argumentation. Stephen Toulmin is professor of Linguistic Philosophy Studies at Cambridge University. He develops six concepts for examine argumentation namely data, claim, warrants, backing, qualifier and rebuttal. Dialectically, its six concepts is related each other to form an argumentation. A good argumentation, as Toulmin’s opinion, is arranged from factual and objective data, supported by strong warrants and backing, truthful qualifier, and can defend from rebuttal. As one of result, this research shows that the correlation between data and claim in MUI’s book categorized as unilateral fact that produces negative issues and impacts to discriminative action for Shi’a community. Keywords: Indonesian Shi’a, Stephen Toulmin, Theory of Argument Abstrak Perdebatan mengenai Syiah di Indonesia meningkat seiring dengan meruncingnya kontestasi geopolitik di Timur Tengah, khususnya yang diwakili oleh Saudi Arabia dan Iran. Konflik Syiah di Indonesia mencapai puncaknya ditandai dengan pengusiran sebagian kelompok Syiah dari tempat tinggal dan kampung halamannya. Perbuatan diskriminatif atas komunitas Syiah itu kemudian mendapatkan legitimasi dengan terbit dan beredarnya buku atas nama MUI pusat yang berjudul Mengenal dan Mewaspadai Penyimpangan Syi’ah di Indonesia. Artikel ini hendak meninjau ulang bangunan wacana dalam buku tersebut dengan perspektif filsafat linguistik, tepatnya menggunakan teori argumentasi yang digagas oleh Stephen Toulmin. Sebuah wacana argumentatif dapat disebut baik, menurut Toulmin, apabila data yang disajikan merupakan fakta bersifat objektif yang didukung oleh warrant dan backing yang kuat, jujur atas qualifier, serta dapat mempertahankan diri dari rebuttal. Salah satu kesimpulan penelitian menunjukkan bahwa korelasi antara data dan claim dalam buku MUI tentang Syiah dikategorikan sebagai fakta sepihak yang melahirkan isu negatif dan dapat berimplikasi pada sikap diskriminatif terhadap komunitas syiah. Kata Kunci: Syiah Indonesia, Stephen Toulmin, Teori Argumentasi.